Numerical Analysis of Fluid‒solid Interactions in a 3D Piezoelectric Micropump Featuring a Passive Check Valve - Y. F. Zhang; B. Zhou; Z. L. Deng (Journal of Applied Fluid Mechanics)
Piezoelectric micropumps have attracted considerable research attention due to their low production cost, compact size, and controllable output performance. However, the fluid-structure interaction mechanisms in passive check valve-based piezoelectric micropumps remain insufficiently understood, leading to gaps in the current understanding of how their flow characteristics influence overall performance. This study addresses these gaps by establishing a flow model for a typical cantilever valve piezoelectric micropump, considering the effects of fluid-structure interaction. Numerical simulations were performed to investigate the flow field, pressure distribution within the pump chamber, and the dynamic behavior of the check valve during operation. The simulations revealed that the mechanical inertia of the valve causes its opening to lag behind the fluid pressure wave propagation, leading to a phase difference between the piezoelectric actuator and the valve. This delay results in transient backflow during the valve's state transition, which negatively impacts the micropump's overall performance by reducing efficiency. Furthermore, the influences of valve dimensions, pump chamber size, piezoelectric actuator size, as well as external driving voltage and frequency on the pump's operational characteristics were systematically analyzed and optimized. Following the optimization process, the micropump's output flow rate increased to 34.02 mL/min, representing a 54.54% improvement over its initial design, demonstrating the substantial performance gains achieved through structural refinement.